Nomenklatur Baru Pendidikan Islam di Era Industrialisasi - Masdar Hilmy (TSAQAFAH, 2012)
The coming of  industrialization era  is irreversible, albeit the rejection by some. Among Muslims, industrialization  is responded differently; some welcome while some others reject uncritically the logics behind the industrialization process. Whether like ordislike, sooner or later, Muslims in the end must live by industrialization era. What the Muslims need  in  response  to  the coming of   industrialization era  is  to  formulate a workable blue-print with which Muslims feel comfortable as an epistemological foundation of the Muslim  faith.  Such a blue-print  is  expected  to be able  to cope with  the ontological, epistemological and  axiological problems  created by  existing  industrialization process.Industrialization process, in my argument, should have not deprived the existential being of   the Muslim  society. The  fact  is  that  the  industrialization projects  result  in  the dehumanizing people. A proper  industrialization must place people as the subject, not the object, of  the  entire process of  industrialization. Far  from  an ambition  to present a complete solution to the current crises faced by Muslims, the need to formulate a new blue-print of  industrialization-based Islamic education will be elaborated by this paper.